A packaging film for secondary batteries, a packaging bag, a secondary battery, and an electronic device
Patent Information
- Application Number
- CN202211212686.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-30
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-09-30
AI Technical Summary
但双面热熔胶的设置,一方面易导致锂离子电池出现顶封冲开,以及卷绕结构的电极组件外圈集流体(如铝箔)撕裂等问题,影响锂离子电池的跌落性能及封装性能;一方面使锂离子电池体积增大,易影响锂离子电池的能量密度
[0024] Of course, implementing any product or method of this application does not necessarily require achieving all of the advantages described above at the same time.
Smart Images

Figure CN117855699B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of electrochemical technology, and in particular to a packaging film, packaging bag, secondary battery, and electronic device for secondary batteries. Background Technology
[0002] Secondary batteries, such as lithium-ion batteries, are widely used in smartphones, wearable devices, consumer drones, and electric vehicles due to their advantages such as high energy density, long cycle life, and no memory effect. With the widespread application of lithium-ion batteries in these fields, the market is placing increasingly higher demands on their overall performance, such as higher energy density, better drop resistance, cycle life, and packaging performance, and less lithium plating.
[0003] When lithium-ion batteries are subjected to external impacts, such as drops, relative displacement can easily occur between the electrode assembly and the packaging bag, affecting the drop performance of the lithium-ion battery. Current technology often uses double-sided hot melt adhesive to improve the drop performance of lithium-ion batteries. However, the use of double-sided hot melt adhesive can lead to problems such as the top seal breaking open and tearing of the outer current collector (e.g., aluminum foil) of the wound electrode assembly, affecting both drop performance and packaging performance. Furthermore, it increases the size of the lithium-ion battery, potentially affecting its energy density.
[0004] High-energy-density lithium-ion batteries often suffer from electrolyte swelling in the main body or corners to ensure sufficient electrolyte supply, affecting their energy density. Furthermore, byproducts of electrolyte reactions in lithium-ion batteries can react with the positive or negative electrode, obstructing lithium-ion insertion / extraction pathways and causing lithium plating, thus impacting the battery's cycle performance and lithium plating resistance.
[0005] Therefore, developing a lithium-ion battery with high overall performance has become a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention
[0006] The purpose of this application is to provide a packaging film, packaging bag, secondary battery, and electronic device for secondary batteries to improve the overall performance of secondary batteries.
[0007] It should be noted that while this application uses lithium-ion batteries as an example of secondary batteries to explain the invention, the secondary batteries in this application are not limited to lithium-ion batteries. The specific technical solution is as follows:
[0008] This application provides a packaging film for secondary batteries, comprising a fiber layer and a heat-sealing layer, wherein the fiber layer is disposed on any surface of the heat-sealing layer along its thickness direction. The fiber layer in the packaging film can store the electrolyte in the secondary battery, alleviate the degree of electrolyte swelling, reduce the electrolyte swelling coefficient, and adsorb byproducts (such as impurity gases or particulate precipitates) generated by the electrolyte after electrolyte injection or during the formation process, reducing the risk of byproducts entering the secondary battery. When this packaging film is used to prepare packaging bags for secondary batteries, it can alleviate lithium plating in the secondary battery and improve the energy density, cycle performance, and lithium plating performance of the secondary battery. Meanwhile, the fiber layer is compressible. When the packaging bag made from the packaging film for secondary batteries is applied to the secondary batteries, after the secondary battery is heat-pressed, the thickness of the compressed area of the fiber layer adjacent to the electrode assembly becomes thinner, while the uncompressed area of the fiber layer not adjacent to the electrode assembly maintains its original thickness. At the boundary between the compressed and uncompressed areas of the fiber layer, the uncompressed area forms a covering structure for the electrode assembly. When the secondary battery is subjected to mechanical impact, this covering structure can restrict the movement of the electrode assembly inside the packaging bag. The uncompressed area of the fiber layer can also act as a buffer layer, reducing the mechanical impact force on the secondary battery and lowering the probability of the packaging bag being blown open. In this way, without increasing the volume of the secondary battery, it can replace the existing double-sided hot melt adhesive, restricting the relative displacement between the electrode assembly and the packaging bag, thereby improving the energy density, encapsulation performance, and drop performance of the secondary battery. Therefore, using the packaging film made from the secondary battery to prepare packaging bags and applying them to secondary batteries improves the overall performance of the secondary battery, such as energy density, cycle performance, and encapsulation performance.
[0009] In some embodiments of this application, the specific surface area of the fiber layer is 2m². 2 / g to 55m 2 / g. Controlling the specific surface area of the fiber layer within the above range is more conducive to improving the cycle performance and lithium plating performance of the secondary battery.
[0010] Preferably, the specific surface area of the fiber layer is 20m². 2 / g to 35m 2 / g. By controlling the specific surface area of the fiber layer within the above-mentioned preferred range, the cycle life and lithium plating performance of the secondary battery are improved.
[0011] In some embodiments of this application, the fibers in the fiber layer are columnar fibers, the porosity of the fiber layer is p0%, 20≤p0≤90; the diameter of the fibers in the fiber layer is dμm, 0.4≤d≤3; and the number of fiber layers in the fiber layer is c, 4≤c≤15. When the porosity p0 of the fiber layer, the diameter d of the fibers in the fiber layer, and the number of fiber layers c in the fiber layer are simultaneously controlled within the above ranges, the secondary battery exhibits good comprehensive performance, such as energy density, cycle performance, drop performance, encapsulation performance, and lithium plating performance.
[0012] Preferably, 50 ≤ p0 ≤ 70, 1 ≤ d ≤ 3, and 10 ≤ c ≤ 15. When the porosity p0 of the fiber layer, the diameter d of the fibers in the fiber layer, and the number of fiber layers c in the fiber layer are simultaneously controlled within the above-mentioned preferred ranges, the secondary battery exhibits good overall performance (e.g., energy density, cycle performance, drop performance, encapsulation performance, and lithium plating performance). Furthermore, the energy density, encapsulation performance, and drop performance of the secondary battery can be further improved.
[0013] Preferably, 20 ≤ p0 ≤ 90, 0.4 ≤ d ≤ 2, and 5 ≤ c ≤ 10. When the porosity p0 of the fiber layer, the diameter d of the fibers in the fiber layer, and the number of fiber layers c in the fiber layer are simultaneously controlled within the above-mentioned preferred ranges, the secondary battery exhibits good overall performance (e.g., energy density, cycle performance, drop performance, encapsulation performance, and lithium plating performance). Furthermore, the energy density, encapsulation performance, and drop performance of the secondary battery are further improved.
[0014] Preferably, 40 ≤ p0 ≤ 60, 0.4 ≤ d ≤ 1, and 5 ≤ c ≤ 10. When the porosity p0 of the fiber layer, the diameter d of the fibers in the fiber layer, and the number of fiber layers c in the fiber layer are simultaneously controlled within the above-mentioned preferred ranges, the secondary battery exhibits good overall performance (e.g., energy density, cycle performance, drop performance, encapsulation performance, and lithium plating performance). Furthermore, the performance stability of the secondary battery, such as cycle performance and lithium plating performance, is further improved.
[0015] In some embodiments of this application, the compression rate of the fiber layer is y0%. 12≤y0≤80. By coordinating the porosity of the fiber layer, the diameter of the fibers in the fiber layer, and the number of layers, the compressibility of the fiber layer is controlled within the above range, thereby improving the overall performance of the secondary battery, such as energy density, cycle performance, drop performance, encapsulation performance, and lithium plating performance.
[0016] In some embodiments of this application, the initial thickness of the fiber layer is T0 μm. After hot pressing at a temperature of 65°C to 90°C and a pressure of 0.3 MPa to 2.0 MPa, the final thickness of the fiber layer is T1 μm, where 2 ≤ T0-T1 ≤ 30 and 0<T1 ≤ 30. By controlling the values of T0-T1 and T1 within the above ranges, the energy density, encapsulation performance, and drop performance of the secondary battery can be further improved.
[0017] In some embodiments of this application, the materials for the fiber layer and the heat-sealing layer are each independently selected from at least one of polyethylene, modified polypropylene, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-vinyl acetate-vinyl alcohol terpolymer, ethylene-propylene-1-butene polymer, polyethylene terephthalate, polyurethane, or polyamide. When the fiber layer and heat-sealing layer are selected from the above materials, they have suitable encapsulation melting points, thereby improving the encapsulation performance of the secondary battery when the packaging bag made from the packaging film is applied to the secondary battery.
[0018] In some embodiments of this application, the fiber layer and the heat-sealing layer are made of the same material. When the fiber layer and the heat-sealing layer are made of the same material, the material consistency between the heat-sealing layer and the fiber layer reduces the risk of foreign matter generation. Therefore, when the packaging bag made of the packaging film for secondary batteries is used in secondary batteries, it is more beneficial to the encapsulation performance of the secondary batteries.
[0019] In some embodiments of this application, the packaging film for secondary batteries further includes a metal layer and a protective layer, with the fiber layer, heat-sealing layer, metal layer, and protective layer sequentially stacked. In some embodiments of this application, the metal layer is aluminum foil or steel foil. In some embodiments of this application, the protective layer includes at least one of polyamide, polyethylene terephthalate, polypropylene, or polyethylene.
[0020] The second aspect of this application provides a packaging bag made from the packaging film for secondary batteries provided in the first aspect of this application. Therefore, applying the packaging bag to secondary batteries can improve the overall performance of the secondary batteries, such as energy density, cycle performance, drop performance, encapsulation performance, and lithium plating performance.
[0021] A third aspect of this application provides a secondary battery comprising an electrode assembly and a packaging bag as provided in the second aspect of this application, wherein the electrode assembly is contained within the packaging bag.
[0022] In some embodiments of this application, the packaging bag includes a heat-sealed portion and a receiving portion. The receiving portion is formed by heat-sealing a fiber layer and a heat-sealing layer located in the heat-sealed portion. The electrode assembly is placed in the receiving portion, and the electrode assembly is adjacent to the fiber layer located in the receiving portion. Therefore, the secondary battery has good overall performance, such as energy density, cycle performance, drop performance, encapsulation performance, and lithium plating performance.
[0023] A fourth aspect of this application provides an electronic device that includes the secondary battery provided in the third aspect of this application. Therefore, the electronic device possesses excellent overall performance, such as energy density, cycle performance, drop performance, packaging performance, and lithium plating performance.
[0024] Of course, implementing any product or method of this application does not necessarily require achieving all of the advantages described above at the same time. Attached Figure Description
[0025] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other embodiments can be obtained based on these drawings.
[0026] Figure 1 This is a schematic diagram of the packaging film structure for secondary batteries according to some embodiments of this application;
[0027] Figure 2 The following are schematic diagrams of the secondary battery structure according to some embodiments of this application;
[0028] Figure 3 Scanning electron microscope (SEM) images of fiber layers from some embodiments of this application;
[0029] Figure 4 This is a schematic diagram illustrating the process of in-situ adsorption and removal of byproducts by the fiber layer in some embodiments of this application;
[0030] Figure 5 The following are schematic diagrams of the secondary battery structure according to some embodiments of this application;
[0031] Figure 6 This is a cross-sectional view of the packaging film for secondary batteries along its thickness direction, according to some other embodiments of this application.
[0032] Figure 7 This is a schematic diagram showing the bonding relationship of the hot melt adhesive between the electrode assembly and the packaging bag in Comparative Example 1.
[0033] Figure 8 This is a schematic cross-sectional view of the fiber layer along its own thickness direction in some embodiments of this application. Detailed Implementation
[0034] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art based on this application are within the scope of protection of this application.
[0035] This application provides a packaging film for secondary batteries, comprising a fiber layer and a heat-sealing layer, wherein the fiber layer is disposed on any surface of the heat-sealing layer along its thickness direction. That is, the fiber layer is disposed on one of the two surfaces of the heat-sealing layer along its thickness direction. For example, as... Figure 1 As shown, the packaging film 001 for secondary batteries includes a fiber layer 10 and a heat-sealing layer 20. The fiber layer 10 is disposed on a first surface 20a of the heat-sealing layer 20 along its own thickness direction. In some embodiments of this application, the fiber layer 10 may also be disposed on a second surface 20b of the heat-sealing layer 20 along its own thickness direction.
[0036] The fiber layer in the packaging film for secondary batteries in this application, with its unique high specific surface area and porous structure, can store the electrolyte in the secondary battery, alleviate the degree of electrolyte swelling, reduce the swelling coefficient, and adsorb by-products (such as impurity gases or particulate precipitates) generated by the electrolyte after electrolyte injection or during the formation process, reducing the risk of by-products entering the secondary battery. Applying the packaging film to secondary batteries as a packaging bag can alleviate lithium plating and improve the energy density, cycle performance, and lithium plating performance of the secondary battery. During secondary battery encapsulation, the fiber layer typically functions similarly to the heat-sealing layer, both serving to encapsulate the secondary battery. Furthermore, the fiber layer, located on the surface of the heat-sealing layer, can accelerate the melting process of the heat-sealing material, improving the encapsulation effect of the secondary battery. Simultaneously, the fiber layer has compressibility, allowing the packaging bag made from the packaging film to be used in secondary batteries. Figure 2As shown, after the secondary battery undergoes hot-pressing treatment, the thickness of the fiber layer in the pressure-bearing region 102 adjacent to the electrode assembly 002 decreases, while the thickness of the fiber layer in the unpressure-bearing region 101 not adjacent to the electrode assembly 002 remains unchanged. At the boundary between the pressure-bearing region 102 and the unpressure-bearing region 101, the unpressure-bearing region 101 forms a covering structure for the electrode assembly 002. When the secondary battery is subjected to mechanical impact, this covering structure can restrict the movement of the electrode assembly inside the packaging bag. The unpressure-bearing region can also act as a buffer layer, reducing the mechanical impact force on the secondary battery and lowering the probability of the packaging bag being broken open. In this way, without increasing the volume of the secondary battery, it can replace the existing double-sided hot melt adhesive, restricting the relative displacement between the electrode assembly and the packaging bag, thereby improving the energy density, encapsulation performance, and drop performance of the secondary battery. Therefore, by preparing packaging bags from packaging film and applying them to secondary batteries, the overall performance of the secondary battery is improved, such as energy density, cycle performance, and encapsulation performance.
[0037] In some embodiments of this application, the specific surface area of the fiber layer is 2m². 2 / g to 55m 2 / g, preferably 20m 2 / g to 35m 2 / g. For example, the specific surface area of the fiber layer can be 2m². 2 / g、5m 2 / g, 10m 2 / g、20m 2 / g、30m 2 / g、35m 2 / g、45m 2 / g、55m 2 / g or any value between any two of the above ranges. The specific surface area of the fiber layer is too small (e.g., less than 2m²). 2 If the specific surface area of the fiber layer is too large (e.g., greater than 55 m² / g), the electrolyte storage capacity and the adsorption capacity of by-products will be affected. This will make the secondary battery more prone to electrolyte swelling, increasing the risk of by-products entering the battery and thus impacting its cycle performance and lithium plating performance. 2 The thinner fiber material per unit volume ( / g) limits its processability and strength for widespread application. Controlling the specific surface area of the fiber layer within the aforementioned range is more beneficial for improving the cycle performance and lithium plating performance of the secondary battery. Furthermore, controlling the specific surface area of the fiber layer within the aforementioned preferred range enhances its electrolyte storage capacity and byproduct adsorption capacity, thereby improving the cycle performance and lithium plating performance of the secondary battery.
[0038] This application does not impose any particular limitation on the structure of the fibers in the fiber layer, as long as it achieves the purpose of this application. For example, the structure of the fibers in the fiber layer can be columnar fibers. Exemplarily, Figure 3 SEM images of the fiber layer in some embodiments of this application are shown. Alternatively, the fiber structure in the fiber layer may be any of the following: a porous structure with a certain volume and strength plasticity. This application does not have specific limitations on the porous structure with a certain volume and strength plasticity, as long as it can achieve the purpose of this application.
[0039] In some embodiments of this application, the fibers in the fiber layer are columnar fibers, the porosity of the fiber layer is p0%, 20≤p0≤90; the diameter of the fibers in the fiber layer is dμm, 0.4≤d≤3; and the number of fiber layers in the fiber layer is c, 4≤c≤15. For example, p0 can be 20, 30, 40, 50, 60, 70, 80, 90, or any value between any two of the above ranges; d can be 0.4, 1, 1.5, 2, 2.5, 3, or any value between any two of the above ranges; and c can be 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, or any value between any two of the above ranges. When the porosity p0 of the fiber layer, the diameter d of the fibers in the fiber layer, and the number of fiber layers c in the fiber layer are simultaneously controlled within the above ranges, the secondary battery exhibits good comprehensive performance, such as energy density, cycle performance, drop performance, encapsulation performance, and lithium plating performance.
[0040] Preferably, in some embodiments of this application, 50≤p0≤70; 1≤d≤3; 10≤c≤15. For example, p0 can be 50, 60, 70, 80, 90, or any value between any two of the above ranges; d can be 1, 1.5, 2, 2.5, 3, or any value between any two of the above ranges; and c can be 10, 11, 12, 13, 14, 15, or any value between any two of the above ranges. When the porosity p0 of the fiber layer, the diameter d of the fiber in the fiber layer, and the number of fiber layers c in the fiber layer are simultaneously controlled within the above preferred ranges, the secondary battery has good comprehensive performance (e.g., energy density, cycle performance, drop performance, encapsulation performance, and lithium plating performance). Furthermore, the depth of the fiber layer limiting mechanism, i.e., the thickness difference between the compressed area and the uncompressed area of the fiber layer, is further increased, the mechanical tensile strength of the fiber layer is improved, and the fiber layer can reduce the intensity of local impact force on the electrode assembly, thus reducing the mechanical impact force on the secondary battery. Meanwhile, it can replace existing double-sided hot melt adhesive without increasing the size of the secondary battery, thus limiting the relative displacement between the electrode assembly and the packaging bag. As a result, the energy density, encapsulation performance, and drop resistance of the secondary battery can be further improved.
[0041] Preferably, in some embodiments of this application, 20 ≤ p0 ≤ 90; 0.4 ≤ d ≤ 2; 5 ≤ c ≤ 10. For example, p0 can be 20, 30, 40, 50, 60, 70, 80, 90, or any value between any two of the above ranges; d can be 0.4, 1, 1.5, 2, or any value between any two of the above ranges; and c can be 5, 6, 7, 8, 9, 10, or any value between any two of the above ranges. When the porosity p0 of the fiber layer, the diameter d of the fiber in the fiber layer, and the number of fiber layers c in the fiber layer are simultaneously controlled within the above preferred ranges, the secondary battery exhibits good comprehensive performance (e.g., energy density, cycle performance, drop performance, encapsulation performance, and lithium plating performance). Furthermore, the liquid absorption capacity of the fiber layer pore structure increases. The inventors have found that when packaging bags prepared from packaging films for secondary batteries are applied to secondary batteries, the liquid absorption capacity of both the pressure-bearing and non-pressure-bearing areas of the fiber layer increases, with the liquid absorption capacity of the non-pressure-bearing area of the fiber layer approaching 100%. Therefore, the fiber layer can store electrolyte, alleviating the degree of electrolyte swelling in the secondary battery and reducing the swelling coefficient. This reduces the battery thickness and increases its energy density. The absorbed fiber layer can also combine with the electrolyte, acting as a buffer layer to reduce the impact force on the secondary battery during mechanical shocks, lowering the probability of the packaging bag breaking open. Consequently, the energy density, encapsulation performance, and drop resistance of the secondary battery are further improved.
[0042] Preferably, in some embodiments of this application, 40 ≤ p0 ≤ 60; 0.4 ≤ d ≤ 1; 5 ≤ c ≤ 10. For example, p0 can be 40, 50, 60, or any value between any two of the above ranges; d can be 0.4, 0.6, 0.8, 1, or any value between any two of the above ranges; and c can be 5, 6, 7, 8, 9, 10, or any value between any two of the above ranges. When the porosity p0 of the fiber layer, the diameter d of the fiber in the fiber layer, and the number of fiber layers c in the fiber layer are simultaneously controlled within the above preferred ranges, the secondary battery exhibits good comprehensive performance (e.g., energy density, cycle performance, drop performance, encapsulation performance, and lithium plating performance). In existing technologies, after electrolyte injection or during the formation process of a secondary battery, a large number and variety of byproducts, such as gaseous or particulate precipitates, are generated upon contact between the electrolyte and the electrode components. These byproducts can migrate with the electrolyte into the secondary battery, forming localized accumulations and creating more complex byproducts. This affects lithium-ion transport, exacerbates lithium plating, and negatively impacts battery performance, such as cycle life and lithium plating performance. Furthermore, the fiber layer possesses excellent adsorption properties, enabling the adsorption of byproducts. During the secondary battery encapsulation process, these byproducts are discharged along with excess electrolyte. For example, Figure 4The diagram illustrates a process for in-situ adsorption and removal of byproducts by a fiber layer in some embodiments of this application. Figure 4 (a) shows that byproduct 003 generated after secondary battery electrolyte injection is adsorbed by fiber layer 10 along the direction of the arrow, and then as shown in Figure 10. Figure 4 As shown in (b), after the secondary battery is formed, the byproduct 003 is pushed to both ends of the electrode assembly 002 in the direction of the arrow. The byproduct 003 accumulates in the fiber layer 10 adjacent to both ends of the electrode assembly 002. Finally, as shown in (b), Figure 4 As shown in (c), during the encapsulation of the secondary battery, byproduct 003 is discharged along with excess electrolyte. This allows for the removal of byproducts from within the secondary battery, reducing their impact on battery performance. Consequently, the performance stability of the secondary battery, such as cycle performance and lithium plating performance, is further improved.
[0043] In some embodiments of this application, the compression rate of the fiber layer is y0%. 12 ≤ y0 ≤ 80. For example, y0 can be 12, 20, 30, 40, 50, 60, 70, 80, or any value between any two of the above ranges. By coordinating the porosity of the fiber layer, the diameter of the fibers in the fiber layer, and the number of layers, the compressibility of the fiber layer is controlled within the above range. The packaging film for the secondary battery is then used to prepare a packaging bag for the secondary battery. After the fiber layer is compressed by hot-pressing the secondary battery, the thickness of the compressed area of the fiber layer becomes thinner. At the boundary between the compressed and uncompressed areas of the fiber layer, the uncompressed area forms a covering structure for the electrode assembly. When the secondary battery is subjected to mechanical impact, this covering structure can restrict the movement of the electrode assembly inside the packaging bag. The uncompressed area of the fiber layer can also act as a buffer layer, reducing the mechanical impact force on the secondary battery and lowering the probability of the packaging bag being broken open. In this way, without increasing the volume of the secondary battery, it can replace the existing double-sided hot melt adhesive, restricting the relative displacement between the electrode assembly and the packaging bag, thereby improving the energy density, encapsulation performance, and drop performance of the secondary battery. Meanwhile, the high specific surface area and porous structure of the fiber layer can store the electrolyte in the secondary battery, alleviating the degree of electrolyte swelling, reducing the swelling coefficient, and adsorbing byproducts (such as impurity gases or particulate precipitates) generated by the electrolyte after electrolyte injection or during the formation process, reducing the risk of byproducts entering the secondary battery. Applying the packaging film to secondary batteries as packaging bags can alleviate lithium plating and improve the energy density, cycle performance, and lithium plating performance of the secondary battery. Therefore, applying the packaging film to secondary batteries as packaging bags improves the overall performance of the secondary battery, such as energy density, cycle performance, drop performance, encapsulation performance, and lithium plating performance.
[0044] In some embodiments of this application, the initial thickness of the fiber layer is T0 μm. After hot pressing at a temperature of 65°C to 90°C and a pressure of 0.3 MPa to 2.0 MPa, the final thickness of the fiber layer is T1 μm, where 2 ≤ T0 - T1 ≤ 30 and 0 < T1 ≤ 30. Preferably, 10 ≤ T0 - T1 ≤ 30 and 15 ≤ T1 ≤ 30. For example, the value of T0 - T1 can be 2, 6, 10, 14, 16, 18, 20, 30, or any value between any two of the above ranges, and the value of T1 can be 0.1, 1, 5, 10, 15, 20, 25, 30, or any value between any two of the above ranges. Adjusting the values of T0 - T1 and T1 within the above ranges, such as... Figure 5 As shown, the thickness difference between the final thickness T1 of the fiber layer 10 in the compressed region 102 and the initial thickness T0 of the fiber layer 10 in the uncompressed region 101 further increases, improving the mechanical tensile strength of the fiber layer 10. The fiber layer 10 can reduce the intensity of local impact forces on the electrode assembly 002, thus reducing the mechanical impact force on the secondary battery. Simultaneously, it can replace existing double-sided hot melt adhesive without increasing the volume of the secondary battery, limiting the relative displacement between the electrode assembly and the packaging bag. Therefore, the energy density, encapsulation performance, and drop performance of the secondary battery are further improved. This application does not impose any particular limitation on the value of the initial thickness T0 of the fiber layer, as long as it achieves the purpose of this application. For example, T0 can be from 2 μm to 45 μm.
[0045] In this application, the compression ratio of the fiber layer = (initial thickness of the fiber layer - final thickness of the fiber layer) / initial thickness of the fiber layer × 100% = (T0 - T1) / T0 × 100%. Here, the initial thickness of the fiber layer can be understood as the thickness before compression, and the final thickness of the fiber layer can be understood as the thickness after compression.
[0046] This application does not impose any particular limitation on the thickness of the heat-sealing layer, as long as it achieves the purpose of this application. For example, the thickness of the heat-sealing layer can be from 15 μm to 60 μm.
[0047] In some embodiments of this application, the materials for the fiber layer and the heat-sealing layer are each independently selected from at least one of polyethylene (PE), modified polypropylene (PP), ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-vinyl acetate-vinyl alcohol terpolymer, ethylene-propylene-1-butene polymer, polyethylene terephthalate (PET), polyurethane, or polyamide. When the fiber layer and heat-sealing layer are selected from the above materials, they have suitable encapsulation melting points, thereby improving the encapsulation performance of the secondary battery when the packaging bag made from the packaging film is applied to the secondary battery.
[0048] This application does not impose any particular limitation on the weight-average molecular weight of the above-mentioned materials, as long as they can achieve the purpose of this application. For example, the weight-average molecular weight is between 500,000 and 8,000,000.
[0049] In some embodiments of this application, the fiber layer and the heat-sealing layer are made of the same material. When the fiber layer and the heat-sealing layer are made of the same material, the material consistency between the heat-sealing layer and the fiber layer reduces the risk of foreign matter generation. Therefore, when the packaging bag made of the packaging film for secondary batteries is used in secondary batteries, it is more beneficial to the encapsulation performance of the secondary batteries.
[0050] In some embodiments of this application, the packaging film for secondary batteries further includes a protective layer and a metal layer, wherein the protective layer, metal layer, heat-sealing layer, and fiber layer are stacked sequentially. For example, as shown... Figure 6 As shown, the packaging film 001 for secondary batteries includes a fiber layer 10, a heat-sealing layer 20, a metal layer 30, and a protective layer 40 stacked sequentially. This application does not impose any particular limitation on the materials of the protective layer and the metal layer, as long as they achieve the purpose of this application. For example, the material of the protective layer may include high-melting-point (melting point 115°C to 135°C) polyethylene terephthalate, nylon (polyamide), or polyolefin materials (such as polypropylene, polyethylene). The material of the protective layer has strong mechanical properties, which can prevent external forces from damaging the lithium-ion battery, thus protecting the lithium-ion battery. The material of the metal layer may be any one of aluminum foil, steel foil, or titanium foil, which can prevent the penetration of external moisture into the lithium-ion battery and prevent the leakage of internal electrolyte. This application does not impose any particular limitation on the thickness of the protective layer and the metal layer, as long as they achieve the purpose of this application. For example, the thickness of the protective layer may be 15 μm to 25 μm, and the thickness of the metal layer may be 20 μm to 40 μm.
[0051] This application does not impose any particular limitation on the preparation method of the packaging film for secondary batteries, as long as it can achieve the purpose of this application. For example, traditional co-extrusion lamination and thermoplastic fiber meltblown molding methods known in the art can be used.
[0052] The second aspect of this application provides a packaging bag made from the packaging film for secondary batteries provided in the first aspect of this application. Therefore, applying the packaging bag to secondary batteries can improve the overall performance of the secondary batteries, such as energy density, cycle performance, drop performance, encapsulation performance, and lithium plating performance.
[0053] This application does not impose any particular restrictions on the method of preparing the packaging bag, as long as it can achieve the purpose of this application.
[0054] A third aspect of this application provides a secondary battery comprising an electrode assembly and a packaging bag as provided in the second aspect of this application, wherein the electrode assembly is contained within the packaging bag.
[0055] In some embodiments of this application, the packaging bag includes a heat-sealed portion and a receiving portion. The receiving portion is formed by heat-sealing a fiber layer and a heat-sealing layer located in the heat-sealed portion. The electrode assembly is placed in the receiving portion, and the electrode assembly is adjacent to the fiber layer located in the receiving portion. Therefore, the secondary battery has good overall performance, such as energy density, cycle performance, drop performance, encapsulation performance, and lithium plating performance.
[0056] This application does not impose any particular restrictions on the structure of the electrode assembly, as long as it achieves the purpose of this application. For example, the structure of the electrode assembly can be a stacked structure or a wound structure.
[0057] The electrode assembly of this application includes a positive electrode, a separator, and a negative electrode. The separator is located between the positive and negative electrode, separating them to prevent internal short circuits in the secondary battery. The separator allows electrolyte ions to pass freely, thus completing the electrochemical charge-discharge process. In this application, the number of separators, positive and negative electrode plates in the electrode assembly is not particularly limited, as long as the purpose of this application is achieved.
[0058] This application does not impose any particular restrictions on the types of positive electrode sheets, separators, and negative electrode sheets. Those skilled in the art can choose according to actual needs, as long as the purpose of this application can be achieved. Exemplarily, in some embodiments of this application, the positive electrode sheet includes a positive active material layer and a positive current collector. The positive active material layer is disposed on one or both surfaces of the positive current collector along its thickness direction, and the positive active material layer includes a positive active material. The negative electrode sheet includes a negative active material layer and a negative current collector. The negative active material is disposed on one or both surfaces of the negative current collector along its thickness direction, and the negative active material layer includes a negative active material. This application does not impose any particular restrictions on the positive active material, positive current collector, negative active material, and negative current collector. Those skilled in the art can choose according to actual needs, as long as the purpose of this application can be achieved.
[0059] The secondary battery of this application also includes an electrolyte. This application does not have any particular restrictions on the electrolyte, and those skilled in the art can choose according to actual needs, as long as it can achieve the purpose of this application.
[0060] The secondary battery described in this application is not particularly limited and may include devices in which an electrochemical reaction occurs. For example, the secondary battery may include, but is not limited to: lithium metal secondary batteries, lithium-ion secondary batteries (lithium-ion batteries), sodium-ion secondary batteries, lithium polymer secondary batteries, and lithium-ion polymer secondary batteries.
[0061] This application does not impose any particular restrictions on the preparation method of the secondary battery. Any preparation method known in the art can be used, as long as it can achieve the purpose of this application.
[0062] A fourth aspect of this application provides an electronic device that includes the secondary battery provided in the third aspect of this application. Therefore, the electronic device possesses excellent overall performance, such as energy density, cycle performance, drop performance, packaging performance, and lithium plating performance.
[0063] The electronic device described in this application is not particularly limited and can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to: laptop computers, pen input computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, electric bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, lithium-ion capacitors, etc.
[0064] Example
[0065] The embodiments and comparative examples provided below illustrate the implementation of this application in more detail. Various tests and evaluations were conducted according to the methods described below.
[0066] Test methods and equipment:
[0067] Test of the specific surface area of the fiber layer:
[0068] Take a piece with an area of 1m 2 The base layer (metal foil + heat-sealing PP layer) without the fiber layer is weighed (M1). The fiber layer is then coated onto the heat-sealing layer and weighed (M2). The weight of the coated fiber layer is m0 = M2 - M1. Using a scanning electron microscope (SEM), the number of fibers (n), the diameter (dμm) of each fiber, and the length (L, in μm) are measured. The surface area A (m²) can then be obtained. 2 )=πd×L×n / 10 -12 Specific surface area B (m²) 2 / g)=A / m0.
[0069] SEM test:
[0070] The fiber layer was tested using a scanning electron microscope (manufacturer: Oxford energy dispersive spectrometer, model: Apero-S / EDS).
[0071] Testing of the porosity of the fiber layer and the diameter of the fibers within the fiber layer:
[0072] Take the cross-section of the packaging bag in each embodiment and comparative example (the cross-section obtained by cutting along the thickness direction of the packaging bag itself), perform SEM scanning, and obtain SEM images. First, determine the area where the fiber layer is located in the SEM image and record this area as region A. The porosity of the fiber layer is obtained through region A. Figure 8 An exemplary structural diagram of region A is given. Porosity p0 = 1 - (n × π × d) 2 / 4) / M0, where n is the number of fibers in region A, d is the average diameter of the fibers in region A, and M0 is the area of region A. n is obtained by direct counting, d is obtained by measurement using size measurement software, and M0 is calculated based on the size scale in the SEM image.
[0073] Testing the number of fiber layers in the fiber layer:
[0074] Cross-sections (sections obtained by cutting along the thickness direction of the packaging bag) of each embodiment and comparative example were taken and SEM scanned to obtain SEM images. The region containing the fiber layers in the SEM images was first determined and denoted as region A. The number of fiber layers, n, was then estimated using region A. Figure 8 A schematic diagram of the structure of region A is given as an example.
[0075] Methods for estimating the number of fiber layers n: such as Figure 8 As shown, in a SEM field of view with a size of 40μm×50μm, the number of fiber layers n is estimated from top to bottom along the Y direction. The topmost fiber is selected as fiber 1, which is called the first layer. The fiber with the largest overlap area with fiber 1 along the X direction is fiber 2, which is called the second layer. The fiber with the largest overlap area with fiber 2 along the X direction is fiber 3, and so on. The above steps are repeated until the bottom layer of the SEM field of view is reached. Figure 8 The fiber layer shown has a fiber layer number n = 5.
[0076] Testing of the initial and final thickness of the fiber layer:
[0077] Take the cross-section of the packaging bag in each embodiment and comparative example (the cross-section obtained by cutting along the thickness direction of the packaging bag itself) and perform SEM scanning to obtain SEM images. First, determine the area where the fiber layer is located in the SEM image and record this area as region A. The dimension of region A along the thickness direction of the packaging bag itself is the initial thickness or the final thickness of the fiber layer. The initial thickness and the final thickness of the fiber layer are measured using dimensional measurement software.
[0078] The initial thickness of the fiber layer was measured using the packaging bags used before the lithium-ion batteries in each embodiment and comparative example. The final thickness of the fiber layer was obtained by measuring the packaging bags obtained after disassembling the lithium-ion batteries in each embodiment and comparative example.
[0079] Cyclic performance testing:
[0080] In an environment of 25°C, the lithium-ion battery was charged at a constant current of 2C to 4.25V, then charged at a constant current of 1C to 4.48V, then charged at a constant voltage of 4.48V to 0.05C, and finally discharged at a constant current of 0.5C to 3.0V; this constitutes one charge-discharge cycle. Then, the same steps were repeated for 1000 charge-discharge cycles.
[0081] Then, the lithium-ion battery is disassembled in a dry room with humidity below 5%, and the state of the negative electrode is recorded by taking photos. If there is no lithium plating, it is considered a pass; if there is lithium plating, it is considered a fail.
[0082] Five lithium-ion batteries were tested in each embodiment or comparative example to characterize cycle performance by dividing the number by 5.
[0083] Packaging performance testing:
[0084] Lithium-ion batteries were subjected to drop tests, with 10 replicates for each embodiment. The lithium-ion battery was placed in a drop clamp and dropped from a height of 1.5m, ensuring that all six planes and four corners of the cubic-shaped battery touched the ground at least once after a free fall; this constituted one round of testing. During the test, the appearance of the lithium-ion battery was inspected; no leakage was considered a pass, and the number of pass batteries was counted. Ten lithium-ion batteries were tested for each embodiment or comparative example, and the number of pass batteries divided by 10 characterized the packaging performance.
[0085] Energy density testing:
[0086] First, charge the lithium-ion battery of Comparative Example 1 according to the following procedure, and then discharge it to obtain the discharge capacity of the lithium-ion battery: charge at a constant current of 3C to 4.45V, then charge at a constant voltage of 4.45V to 0.05C, and let it stand for 5 minutes; discharge at a constant current of 0.5C to 3.0V, and let it stand for 5 minutes to obtain the discharge capacity C1.
[0087] After the lithium-ion battery in Comparative Example 1 was charged, its length L, width W, and height H were measured using a laser thickness gauge, yielding the volume V = L × W × H. Its volumetric energy density (ED1) can be calculated using the following formula: ED1 (Wh / L) = C1 / V.
[0088] The energy density ED of Examples 1 to 20, excluding Comparative Example 1, was measured according to the above steps.
[0089] Energy density increase (%) = (ED-ED1) / ED1×100%.
[0090] Lithium-ion battery thickness testing:
[0091] Measuring instrument: PPG soft-pack battery thickness gauge
[0092] Test process:
[0093] S1. Start the measuring instrument and zero the meter reading;
[0094] S2. Place the lithium-ion battery to be tested on the test bench and adjust it to the measurement position;
[0095] S3. The stable value measured by the measuring instrument under appropriate pressure (700g) is the thickness of the lithium-ion battery.
[0096] Example 1
[0097] <Preparation of the positive electrode>
[0098] LiCoO2 (positive electrode active material), conductive carbon black (conductive agent), and polyvinylidene fluoride (PVDF, weight average molecular weight 850,000) (batch agent) were mixed in a mass ratio of 97.5:1.0:1.5. N-methylpyrrolidone (NMP) was added to prepare a slurry with a solid content of 75 wt%. The mixture was stirred under vacuum until a homogeneous positive electrode slurry was formed. The positive electrode slurry was uniformly coated onto one surface of a positive electrode current collector aluminum foil and dried at 130°C to obtain a positive electrode sheet with a single-sided coating of positive electrode active material. The above steps were then repeated on the other surface of the same aluminum foil to obtain a positive electrode sheet with a double-sided coating of positive electrode active material. After drying at 90°C, the sheet was cold-pressed, cut, and had tabs welded to obtain a positive electrode sheet with dimensions of 74 mm × 867 mm for later use.
[0099] <Preparation of Negative Electrode Sheets>
[0100] Graphite (negative electrode active material), graphite (negative electrode conductive agent), carbon black (negative electrode conductive agent), and polyacrylic acid (weight average molecular weight 350,000) (negative electrode binder) were mixed in a mass ratio of 54:35:1:10. The resulting mixture was uniformly dispersed in distilled water and stirred evenly under vacuum to obtain a negative electrode slurry with a solid content of 75 wt%. The negative electrode slurry was uniformly coated onto one surface of a 12 μm thick copper foil current collector. The copper foil was dried at 85°C to obtain a negative electrode sheet with a single-sided coating of negative electrode active material layer with a coating thickness of 1.5 μm. The above steps were repeated on the other surface of the copper foil to obtain a negative electrode sheet with a double-sided coating of negative electrode active material layer. After drying, cold pressing, cutting, and slitting, a negative electrode sheet with a size of 78 mm × 875 mm was obtained.
[0101] <Preparation of the diaphragm>
[0102] A polyethylene film with a thickness of 7μm was selected.
[0103] <Preparation of Electrolyte>
[0104] In a dry argon atmosphere, dioxane and dimethyl ether are mixed at a mass ratio of 1:1 to obtain an organic solvent. Then, lithium salt bis(trifluoromethanesulfonyl)imide lithium is added to the organic solvent to dissolve and mix evenly to obtain an electrolyte with a lithium salt concentration of 1.0 mol / L.
[0105] <Preparation of Packaging Bags>
[0106] Packaging bags are prepared by punching and cutting packaging film for secondary batteries.
[0107] Among them, the packaging film for secondary batteries is as follows: Figure 6 The structure shown, the packaging film 001 for secondary batteries, includes a fiber layer 10, a heat-sealing layer 20, a metal layer 30, and a protective layer 40 stacked sequentially. The specific surface area of the fiber layer is 55 m² / g. 2 / g, porosity p0 = 20%, columnar structure of fibers in the fiber layer, fiber diameter dμm = 0.4μm, number of fiber layers c = 4, initial thickness T0μm = 30μm, fiber layer material is polypropylene (PP, weight average molecular weight 5000). The heat-sealing layer is made of polypropylene (PP, weight average molecular weight 8000) and has a thickness of 30μm. The metal layer is made of aluminum foil and has a thickness of 35μm. The protective layer is made of nylon (weight average molecular weight 16000) and has a thickness of 20μm.
[0108] <Preparation of Lithium-ion Batteries>
[0109] The positive electrode, separator, and negative electrode prepared above are stacked in sequence, with the separator positioned between the positive and negative electrode to act as a separator, and then wound to obtain an electrode assembly. The electrode assembly is placed in the packaging bag prepared above, and the moisture is removed at 80°C. The prepared electrolyte is then injected, and the battery undergoes vacuum sealing (sealing temperature 170°C, sealing pressure 0.3MPa), settling, formation (hot pressing temperature 78°C, hot pressing pressure 1.1MPa), and shaping processes to obtain a lithium-ion battery. The final thickness T1μm of the fiber layer in the pressure-bearing region of the fiber layer is 20μm.
[0110] Examples 2 to 14
[0111] Except for adjusting the relevant preparation parameters according to Table 1, everything else is the same as in Example 1.
[0112] Comparative Example 1
[0113] Except for the absence of a fiber layer in the <Preparation of Packaging Bags> and the <Preparation of Lithium-ion Batteries>, in which... Figure 7 Except for attaching hot melt adhesive 005 at the indicated position to bond the electrode assembly 002 to the packaging bag 004 as a whole, the rest is the same as in Example 1-1.
[0114] The hot melt adhesive includes a substrate layer and hot melt adhesive layers disposed on two surfaces of the substrate layer. The substrate layer is composed of polyethylene terephthalate (PET, weight average molecular weight of 25,000) and has a thickness of 15 μm. The hot melt adhesive layers are composed of styrene-isoprene-styrene block copolymer (SIS, weight average molecular weight of 210,000) and have a single-layer thickness of 17.5 μm. The total thickness of the hot melt adhesive is 50 μm.
[0115] The preparation and performance parameters of each embodiment and comparative example are shown in Table 1.
[0116]
[0117]
[0118] As can be seen from Examples 1 to 14 and Comparative Example 1, when a secondary battery packaging film with a fiber layer is used to prepare a packaging bag for application in a lithium-ion battery, the bag itself has a thinner thickness, meaning that less electrolyte accumulates in the lithium-ion battery, resulting in a stronger electrolyte storage capacity. The lithium-ion battery has higher energy density, cycle performance, and encapsulation performance, indicating that the lithium-ion battery has higher overall performance.
[0119] The specific surface area of the fiber layer, the porosity p0 of the fiber layer, the diameter d and number of fiber layers c, and the compressibility y0 of the fiber layer generally also affect the overall performance of the lithium-ion battery. As can be seen from Examples 1 to 12, the lithium-ion battery within the scope of this application, with the selected specific surface area, porosity p0, fiber diameter d, number of fiber layers c, and compressibility y0 of the fiber layer, exhibits good overall performance.
[0120] The materials of the fiber layer and heat-sealing layer also typically affect the overall performance of lithium-ion batteries. As can be seen from Examples 13 and 14, lithium-ion batteries using fiber layer and heat-sealing layer materials within the scope of this application exhibit good overall performance.
[0121] In contrast, Comparative Example 1 used a packaging bag without a fiber layer in the lithium-ion battery. This bag was thicker, resulting in more electrolyte buildup in the lithium-ion battery. Consequently, the lithium-ion battery had poorer electrolyte storage capacity and lower energy density, cycle performance, drop performance, encapsulation performance, and lithium plating performance. This indicates that the lithium-ion battery does not have good overall performance.
[0122] The various embodiments in this specification are described in a related manner. The same or similar parts between the various embodiments can be referred to each other. Each embodiment focuses on describing the differences from other embodiments.
[0123] The above description is merely a preferred embodiment of this application and is not intended to limit the scope of protection of this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application are included within the scope of protection of this application.
Claims
1. A secondary battery comprising an electrode assembly and a packaging bag, the electrode assembly being housed within the packaging bag, the packaging bag being made of a packaging film for secondary batteries, the packaging film for secondary batteries comprising a fiber layer and a heat-sealing layer, the fiber layer being disposed on any surface of the heat-sealing layer along its own thickness direction; the fiber structure in the fiber layer being columnar fiber, the porosity of the fiber layer being p0%, 20≤p0≤90; the diameter of the fiber in the fiber layer being d μm, 0.4≤d≤3; the number of fiber layers in the fiber layer being c layers, 4≤c≤15; in, After the fiber layer is compressed by the hot-pressing treatment of the secondary battery, at the junction of the compressed area and the uncompressed area of the fiber layer, the uncompressed area of the fiber layer forms a covering structure for the electrode assembly.
2. The secondary battery according to claim 1, wherein, The specific surface area of the fiber layer is 2 m². 2 / g to 55 m 2 / g.
3. The secondary battery according to claim 1, wherein, The specific surface area of the fiber layer is 20 m². 2 / g to 35 m 2 / g.
4. The secondary battery according to claim 1, wherein, 50≤p0≤70, 1≤d≤3, 10≤c≤15.
5. The secondary battery according to claim 1, wherein, 20≤p0≤90, 0.4≤d≤2, 4≤c≤10.
6. The secondary battery according to claim 1, wherein, 40≤p0≤60, 0.4≤d≤1, 4≤c≤10.
7. The secondary battery according to any one of claims 1 to 6, wherein, The compression rate of the fiber layer is y0%. , 12≤y0≤80.
8. The secondary battery according to claim 7, wherein, The initial thickness of the fiber layer is T0 μm. After hot pressing at a temperature of 65℃ to 90℃ and a pressure of 0.3MPa to 2.0MPa, the final thickness of the fiber layer is T1 μm, where 2≤T0-T1≤30 and 0<T1≤30.
9. The secondary battery according to claim 1, wherein, The materials of the fiber layer and the heat-sealing layer are each independently selected from at least one of polyethylene, modified polypropylene, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-vinyl acetate-vinyl alcohol terpolymer, ethylene-propylene-1-butene polymer, polyethylene terephthalate, polyurethane or polyamide.
10. The secondary battery according to claim 9, wherein, The fiber layer and the heat-sealing layer are made of the same material.
11. The secondary battery according to claim 1, wherein, The packaging film for secondary batteries further includes a metal layer and a protective layer, wherein the fiber layer, the heat-sealing layer, the metal layer and the protective layer are stacked in sequence; The metal layer is aluminum foil or steel foil; The protective layer comprises at least one of polyamide, polyethylene terephthalate, polypropylene, or polyethylene.
12. The secondary battery according to claim 1, wherein, The packaging bag includes a heat-sealing section and a receiving section. The receiving section is formed by heat-sealing the fiber layer and the heat-sealing layer located in the heat-sealing section. The electrode assembly is placed in the receiving section and is adjacent to the fiber layer located in the receiving section.
13. An electronic device comprising the secondary battery of claim 12.
Citation Information
Patent Citations
Lithium-ion secondary battery separator
CN104603981A
Aluminum-plastic film and flexible package battery
CN111640883A